Strategi Distribusi Program Vlogger on The Road dari Voice of America yang ditayangkan oleh BTV - Rizqianthi, Yunita; Tjahjodiningrat, Harry; Undiana, Nala Nandana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The basic idea of this research is the distribution of programs on Indonesian national television. How program programmers from abroad, namely VOA, can broadcast their programs on national television in Indonesia, then the programmer can be assured of having a very good program distribution system, so that it is very interesting and good to be applied to programmers of other television stations, especially in Indonesia. There are two issues raised in this research: distribution techniques and broadcasting policies in Indonesia that must be implemented by VOA. The purpose of this research is to find out the distribution plans and national broadcasting regulations implemented by VOA. This research applies mass media theory and distribution strategy theory using qualitative research methods. The research results show that the strategy carried out by VOA is through direct relations and adjustments by VOA to policies in Indonesia, namely VOA adapts content to make it relevant to issues that are important to Indonesian society. This research can be useful for other television stations in implementing program distribution systems.